Metastasis in neuroblastoma: the MYCN question - Bhavsar, Swapnil Parashram (Frontiers in Oncology, 2023)
Oncogenic drivers like MYCN in neuroblastoma subsets continues to present a significant challenge owing to its strong correlation with high-risk metastatic disease and poor prognosis. However, only a limited number of MYCN-regulatory proteins associated with tumor initiation and progression have been elucidated. In this minireview, I summarize the recent progress in understanding the functional role of MYCN and its regulatory partners in neuroblastoma metastasis.